Detailed insight into chromium species released from failed CoCrMo implants: Ex vivo periprosthetic tissues study - Pechancová, Radka; Gallo, Jiří; Baron, Daniel; Milde, David; Antal, Peter; Slobodová, Zuzana; Lemr, Karel; Pluháček, Tomáš (Journal of biomedical materials research. Part B, Applied biomaterials, 2023)
This unique study provides information on Cr species and their distribution in periprosthetic tissues of patients with metal-on-polyethylene joint implants. Co-Cr-Mo alloy has been widely used in joint replacement and represents a source of metal derived species. In the case of chromium, previous studies on periprosthetic tissues revealed mainly Cr(III) distribution, whereas the potential release of carcinogenic Cr(VI) species has been still a subject of debate. Here, an analytical approach utilizing speciation and fractionation was developed to analyze periprosthetic tissue samples collected from wide range of patients with failed total hip or knee replacements. The results reveal that Cr(III) is mainly released in the form of insoluble CrPO4 and Cr2 O3 particles. The highest Cr contents were found in periprosthetic tissues of patients suffering from aseptic loosening and having more Cr-based implants in the body. Cr species penetrated tissue layers, but their levels decreased with the distance from an implant. The detailed speciation/fractionation study carried out using the set of consecutive periprosthetic tissues of a patient with extensive metallosis showed the presence of trace amounts of free Cr(III), nanoparticles, and metal-protein complexes, but the majority of Cr still occurred in CrPO4 form. Carcinogenic Cr(VI) species were not detected. Up to date, there is no published human tissue study focused on the detailed speciation of both soluble and insoluble Cr-based species in the context of failing total hip and knee replacements.
Keywords: Arthroplasty, Replacement, Knee; totální endoprotéza kolene; Humans; selhání protézy; Metals; aseptic loosening; tissue samples; Arthroplasty, Replacement, Hip; total hip/knee replacement; náhrada kyčelního kloubu; lidé; kovy; Hip Prosthesis; Chromium; chrom; Prosthesis Failure; inductively coupled plasma mass spectrometry; kyčelní protézy; speciation